Significance of isoagglutinin titer in ABO‐incompatible kidney transplantation. Issue 5 (24th December 2013) - Won, Dahae; Choe, Wonho; Kim, Hee‐jung; Kwon, Seog‐Woon; Han, Duck‐Jong; Park, Su‐Kil
<x xml:space="preserve">Abstract</x> ABO‐incompatible (ABO‐i) kidney transplantation (KT) has emerged for overcoming the shortage of organ donors. Although this technique initially achieved only low graft survival due to isoagglutinin, recently developed desensitization protocols have improved survival to levels that are comparable to ABO‐compatible KT. However, isoagglutinin is still regarded as a major obstacle to ABO‐i KT. In this study, we evaluate the impact of isoagglutinin titer on clinical outcomes as well as factors that may influence isoagglutinin titers. In total, data from 95 patients who underwent ABO‐i KT were analyzed. Preoperatively, rituximab administration and plasmapheresis were performed until the titer was reduced to ≤1:4. Retrospective analysis included blood group; timing and dosage of rituximab; isoagglutinin titer; number of plasmapheresis; and clinical outcomes including graft survival and serum creatinine. Graft survival was 95.8% (n = 91) and average serum creatinine at 1‐ and 1.5‐year post‐ABOi‐KT was 1.3. Three patients died of sepsis. The identified predictors of titer‐rebound after transplant were short interval (<7 days) between rituximab and first plasmapheresis (P = 0.004); high initial titer (≥256) (P = 0.023); low titer‐reduction rate (P < 0.001); and blood group O (P < 0.001). One patient who experienced a rebound developed antibody‐mediated rejection. With low‐dose (200 mg) rituximab, the change in isoagglutinin titer‐rebound was not significant and the infection rate was significantly decreased (P = 0.001). In conclusion, isoagglutinin titer‐rebound within the first 2 weeks after KT may be a risk factor for rejection. The factors identified as affecting titer‐rebound after KT were high initial isoagglutinin titer, low titer‐reduction rate, short interval, and blood group O. J. Clin. Apheresis 29:243–250, 2014. © 2013 Wiley Periodicals, Inc.